Relationship with Device use Computer Vision Syndrome in Student - Nurhaerana, Andi Sry; Amir, Suliati P.; Novriansyah, Zulfikri Khalil; Kusumawardhan, Sri Irmandha; Namirah, Hanna Aulia (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Technological progress goes hand in hand with scientific progress. One of the technologies that people are interested in is gadgets. However, even though it was originally created to produce positive benefits, on the other hand it is possible that it could also be used for negative things. This research aims to analyze the relationship between device use and CVS among Pangkep State Madrasah Aliyah students. This research is descriptive with a cross-sectional design. The results showed that 72 people (74.2%) experienced CVS disorders with high intensity of device use, 19 people (19.6%) experienced CVS disorders with moderate intensity of device use, and 6 people (6.2%) experienced CVS disorders with moderate intensity. low device usage. Then as many as 41 people (77.4%) did not experience CVS problems with low intensity of device use and as many as 12 people (22.6%) did not experience CVS problems with moderate intensity of device use, and as many as 6 people (6.2%) didn't experience CVS problems. Furthermore, through the Chi Square test, a significant relationship was found between the use of gadgets and complaints of computer vision syndrome (CVS) in Pangkep State Madrasah Aliyah students as indicated by the p value in the analysis test results of 0.041<0.05.